Thriving as an empath : 365 days of self-care for sensitive people - Orloff, Judith (Sounds True, 2019)
"This daily reader provides 365 days of inspiration, guidance, self-care strategies, and meditative practices. Each entry ends with an intention for the day. Each season of the year has its own introduction outlining the special gifts and challenges of that time of year"--